Reference Notes to Plan and Views of Ancient Remains on the Summit of the Laws, Forfarshire (Proceedings of the Society of Antiquaries of Scotland, 1862)
The author describes the ruined walls on Laws Hill near Monifieth and some of the artefacts that have been found there. The article also includes a plan survey from 1859 with detailed explanatory notes. The Secretary, John Stuart, then adds his own observations of these ruins which he compares to other sites in an attempt to understand their purpose and significance. An an addition to the end of the paper, a report on the ruins from 1827 by Dr John Jamieson offers a description of the site before some of the stones were removed.